Can the prevalence of dental caries be used as an indicator of the quality of dental services? A cross-sectional study among children in Almadinah Almunawwarah, KSA. Issue 1 (February 2016) - Mahrous, Mohamed S.; Bhayat, Ahmed; Hifnawy, Tamer; Bakeer, Hala; Ahmad, Mohamed S.
الملخص: أهداف البحث: تقرير عن حالة تسوس الأسنان والاستفادة من خدمات طب الأسنان للأطفال من سن ٦ إلى١٢ عاما. طرق البحث: أجريت هذه الدراسة التحليلية المقطعية في أربع مدارس ابتدائية في الفترة من يناير إلى مارس ٢٠١٣. تم جمع البيانات الكمية والنوعية باستخدام استبانة بالإضافة إلى فحص الفم السريري. تم تسجيل حالة التسوس خلال فحص الفم السريري باستخدام مؤشرات التدهور، والفقد، و المحشو؛ ومؤشر المتدهور والمفقود والمحشو. النتائج: من العدد الإجمالي ل ٣٨٤ طالبا٬ استجاب ٣٣٠ ( معدل الاستجابة ٨٦٪). كان ثلثا المشاركين (٦٥٪) من الإناث، وكان لديهم تسوس الأسنان أكثر بكثير في كل من الأسنان اللبنية والدائمة مقارنة بالذكور. كان متوسط مؤشر التدهور والمفقود والمحشو للأطفال ٦-١٢ عاما ٤.٩ و ٣.١ على التوالي. وبلغ معدل انتشار تسوس الأسنان بين الأطفال في عمر ٦ أعوام ٨٦٪ وللأطفال في عمر ١٢ عاما ٦٨٪. أفاد جميع المستجيبين باستخدام فرشاة الأسنان بينما أفاد ٢٠٪ بزيارة طبيب الأسنان بانتظام. كان معدل انتشار تسوس الأسنان لأولئك الذين لم يقوموا بزيارة طبيب الأسنان بانتظام ٧٨٪، وذكروا أن "الخوف" (٢٩٪)، وأيضا "لا يوجد سبب لزيارة طبيب الأسنان" (٢٠٪) من أسباب عدم زيارتهم لطبيب الأسنان. من بين من قاموا مؤخرا بزيارة طبيب الأسنان، تم تشخيص ٦٩٪ منهم بالتسوس وكانت طرق العلاج الأكثر شيوعا أخذ الدواء (٥٠٪) والتعليمات عن نظافة الفم (١٩٪). الاستنتاجات: معدل انتشار تسوس الأسنان في هذه الفئة من الأطفال مماثلة لدراسات سابقة أجريت في المملكة العربية السعودية. وما زالت الاستفادة من خدمات طب الأسنان منخفضة إلى حد ما، وهؤلاء الأطفال الذين راجعوا عيادات الأسنان تلقوا الخدمات الوقائية. Abstract : Objectives: To report on the caries status and utilization of dental services of 6- and 12- year-old children. Methods: This cross-sectional analytical study was conducted in four primary schools during January through March 2013. Quantitative and qualitative data were collected by using an interview-based questionnaire and a clinical oral examination. Clinical oral examination recorded caries status using the decayed (D/d), missing (M/m) and filled (F/f) index; Decayed, Missing and Filled Index (DMFT). Results: Of a total of 384 students, 330 responded (response rate of 86%). Two thirds (65%) of participants were females and they had significantly more caries ( p < 0.05) in both primary and permanent dentitions as compared to males. The mean DMFT for 6-year-old and 12-year-old children were 4.9 and 1.3, respectively. The prevalence of caries amongst 6-year-old children was reported to be 86% and that for 12-year-old was 68%. All respondents reported using a toothbrush and 20% claimed to visit a dentist regularly. Those who did not regularly visit a dentist had 78% prevalence of caries and they suggested "fear" (29%) and "no reason to visit a dentist" (20%) as reasons for not visiting a dentist. Of those who recently visited dentists, 69% were diagnosed with caries and the most common treatment modalities received were medication (50%) and oral hygiene instructions (19%). Conclusion: The prevalence of dental caries in this cohort of children was similar to that of earlier studies done in the KSA. The utilization of dental services remained fairly low and those children who did attend dental clinics primarily received preventive services.